PENGARUH AKTIVITAS SHALAT ZUHUR BERJAMAAH TERHADAP PERILAKU PROSOSIAL PADA SISWA KELAS XII DI MAN 3 PALEMBANG - Bagus Hidayattullah; Fajri Ismail; Muhammad Win Afgani (Cross-border, 2023)
This research is Motivated by students who have performed the noon prayer in congregation but do not apply prosocial behavior in the school environment. As is well known that in Islam, prosocial behavior can be demonstrated by worship activities such as congregational prayers, because congregational prayers can strengthen a sense of togetherness, foster affiliation ties to the community, increase social solidarity and unity of thought. This type of research used in this study is a quantitative with a correlational approach aimed at knowing the significance of the effect of the influence of the midday prayer in prosecutorial behavior in class XII students at MAN 3 Palembang. The sampling technique uses the provisions of the Issac and Michael formula with a total of 161 students / subjects. Then the data collection techniques were obtained directly from the research subjects by using measurement tools or data collection tools in the form of scales. Furthermore the data collected has been analyzed using simple regression techniques.